1984
DOI: 10.1067/mva.1984.avs0010727
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular subluxation for high carotid exposure

Abstract: Twenty-four patients with internal carotid artery lesions extending above the second cervical vertebra underwent mandibular subluxation for additional exposure. The original technique of bilateral arch bar wiring requiring 90 minutes for application has evolved into a circummandibular/transnasal wiring technique requiring approximately 10 minutes. Subluxation of the mandibular condyle 10 to 15 mm anteriorly results in displacement of the mandibular ramus 20 to 30 mm anteriorly. This technique provides a marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…The present study objectively demonstrated the efficacy of MS, which was previously only subjectively reported to increase ICA exposure by 5.5-20 mm to the cranial side [3][4][5][7][8][9][10][11]. We found that MS increased mastoid-mandible distance by 5.7 ± 3.1 mm and MIM angle by 13.3 ± 7.9º, and that wire fixation with interdental insertion of Coltoflax ® putty was the most effective technique.…”
Section: Quantitative Findings and Rationale For Msmentioning
confidence: 55%
See 2 more Smart Citations
“…The present study objectively demonstrated the efficacy of MS, which was previously only subjectively reported to increase ICA exposure by 5.5-20 mm to the cranial side [3][4][5][7][8][9][10][11]. We found that MS increased mastoid-mandible distance by 5.7 ± 3.1 mm and MIM angle by 13.3 ± 7.9º, and that wire fixation with interdental insertion of Coltoflax ® putty was the most effective technique.…”
Section: Quantitative Findings and Rationale For Msmentioning
confidence: 55%
“…Moreover, use of an intraluminal shunt requires more distal exposure of the ICA. Various techniques used for CEA in cases of cephalic location of the lesions have been reported, including the retrojugular approach [13], dissection and ligation of the adjacent structures (sternocleidomastoid artery, occipital artery and vein [14,15], ansa cervicalis [14], and posterior belly of the digastric muscle [14,16]), nasotracheal intubation [17], mandibular osteotomy [18,19], elevation of the hypoglossal nerve [1,15,16], and MS [3][4][5][6][7][8][9][10][11]20].…”
Section: Cephalic Location Of Cea and Reported Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major obstacle to access to the distal ICA is the mandibular ramus. Various techniques have been described to improve exposure of the ICA, such as anterior subluxation of the mandible [5][6][7]12) and mandibular osteotomy. 1,2,8,9) However, these techniques are complicated and associated with a high incidence of morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Access to the internal carotid artery (ICA) above the C-2 can be challenging during carotid endarterectomy (CEA), even for experienced surgeons. Improving access to the distal ICA often requires a maneuver such as nasotracheal intubation, 13) extended skin incision, 14) anterior subluxation of the mandible, [5][6][7]12) mandibular osteotomy, 1,2,8,9) retraction or division of the posterior belly of the digastric muscle, 3,4) or division of the styloid process and styloid group of muscles. 11) These techniques may increase exposure, but are time consuming, complicated, and associated with a high incidence of morbidity.…”
Section: Introductionmentioning
confidence: 99%